A Re-assessment of Thomas Hobbes Social Contract Theory and His Concept of Motion - Ekpo, Barnabas David (NIU Journal of Humanities, 2024)
Hobbes held the belief that his political philosophy would resolve political disagreements, rather his work has aroused series of criticisms and oppositions, and has given rise to unending controversies. Thus, this paper is a re-examination of Thomas Hobbes social contract theory and an analysis of his concept of motion. The driving philosophy behind every civil government is the concept of the social contract that spells out the responsibilities of government and duties of the governed. Hobbes was the first who wrote on the social contract where he clearly spelt out how man in the state of nature were life is short, nasty and brutish with no scientific development. Through the dictates of reason man in such a chaotic society was able to form a civil government relinquishing all his rights to this said man or assembly of men in place for law, order and protection. This study employed historic-analytical method. The historical dimension is to provide the knowledge of the political circumstances that prevailed during the time of Hobbes and the analytic aspect is to examine critically the concept of motion in relation to understanding the nature of man. The work concludes that, Hobbes understanding of human nature from the point of view of mechanical and mathematical precision without understanding man from the social human actions and as a conscious being is a major factor that has given rise to series of controversies surrounding his political philosophy. Keywords: Motion, Social Contract, Natural Right, Natural Law and Authority.